− m ≤ x − 2 0 m
Find the smallest value of x which satisfies the above inequality for all non-negative ' m '.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Another way would be to complete the square.
∀ m ∈ R 0 + , ( m ) 2 − 2 0 m + x ≥ 0 ⟺ ( m − 1 0 ) 2 + x ≥ 1 0 0
By the trivial inequality , we have ( m − 1 0 ) 2 ≥ 0 ∀ m ∈ R 0 + . Hence, we have,
x ≥ 1 0 0 − ( m − 1 0 ) 2 ≥ 1 0 0 − 0 = 1 0 0 ⟹ x ≥ 1 0 0
with equality (for all the inequalities so far) iff ( m − 1 0 ) = 0 ⟹ m = 1 0 0 .
Log in to reply
∵ ( m − 1 0 ) 2 ≥ 0 ⇒ 1 0 0 − ( m − 1 0 ) 2 ≤ 1 0 0 and not ≥ 1 0 0
what if M=1, shouldn't then the answer will be x>20 or x=20. why 100 when we can have x=20!?
Log in to reply
But we need to find the smallest value of x such that the given inequality holds true for all non-negative m , and not just m = 1 . For example, the inequality is not true for x = 2 0 , m = 4 .
Problem Loading...
Note Loading...
Set Loading...
We require that m − 2 0 m + x = ( m ) 2 − 2 0 m + x ≥ 0 .
This is a quadratic in m , so the minimum possible value of x that allows this inequality to be satisfied will be such that the discriminant is 0 , , (i.e., when the parabola is tangent to the x -axis). This means that
( − 2 0 ) 2 − 4 x = 0 ⟹ x = 1 0 0 .